2014
DOI: 10.1186/1471-2458-14-352
|View full text |Cite
|
Sign up to set email alerts
|

Untying chronic pain: prevalence and societal burden of chronic pain stages in the general population - a cross-sectional survey

Abstract: BackgroundChronic pain is a major public health problem. The impact of stages of chronic pain adjusted for disease load on societal burden has not been assessed in population surveys.MethodsA cross-sectional survey with 4360 people aged ≥ 14 years representative of the German population was conducted. Measures obtained included demographic variables, presence of chronic pain (based on the definition of the International Association for the Study of Pain), chronic pain stages (by chronic pain grade questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 29 publications
4
50
1
6
Order By: Relevance
“…Medical comorbidities as defined by the Charlson scale were present in more than one‐third of patients. Although these data are broadly consistent with what has been reported in the literature, our results either extend or differ from those in the literature in several respects.…”
Section: Discussionsupporting
confidence: 87%
“…Medical comorbidities as defined by the Charlson scale were present in more than one‐third of patients. Although these data are broadly consistent with what has been reported in the literature, our results either extend or differ from those in the literature in several respects.…”
Section: Discussionsupporting
confidence: 87%
“…In particular, pain may give rise to high levels of distress and even depression (Breivik et al, 2006;Miller and Cano, 2009). Furthermore, research has shown that a substantial number of adults and children/adolescents with chronic pain report high levels of disability (Goubert et al, 2004a;Häuser et al, 2014;Vervoort et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using the Graded Chronic Pain Scale of von Korff and colleagues (1992) have shown that 7.5% to 8.4% of adults reporting persistent (back) pain (Goubert et al, 2004a;Reid et al, 2011;Häuser et al, 2014) function well with high-intensity pain. As well, a recent study in 10650 schoolchildren showed that 19% of children reported pain of high intensity but low disability (Vervoort et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, including studies that focus on health care use, indicate that very large costs are associated with chronic pain and especially severe chronic pain. 12,18,23,27,40 However, very little is known about health care costs in the elderly population. Obviously, the elderly rarely require sick leave, so these costs are marginal.…”
Section: Introductionmentioning
confidence: 99%